2017
DOI: 10.18632/oncotarget.18775
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary folate intake and risks of esophageal, gastric and pancreatic cancers: an overall and dose-response meta-analysis

Abstract: There are still some controversies on the association between dietary folate intake and the risk of upper gastrointestinal cancers including esophageal, gastric and pancreatic cancers. Hence, a comprehensive meta-analysis on all available literatures was performed to clarify the relationship between dietary folate intake and risks of upper gastrointestinal cancers. An electric search was performed up to December 12th, 2016 within the PubMed, MEDLINE AND EMBASE databases. Ultimately, a total of 46 studies which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…This finding is consistent with the results of a recent meta-analysis by Zhao et al [ 11 ]. In the subgroup analysis, there was a geographic-specific difference which suggested that geographic location and/or dietary habits may play an important role in this association [ 9 ]. For example, people living in high-risk regions such as Asia may consume less folate-rich foods (e.g., green leafy vegetables, some fruits, legumes, and liver) compared to people living in low-risk regions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the results of a recent meta-analysis by Zhao et al [ 11 ]. In the subgroup analysis, there was a geographic-specific difference which suggested that geographic location and/or dietary habits may play an important role in this association [ 9 ]. For example, people living in high-risk regions such as Asia may consume less folate-rich foods (e.g., green leafy vegetables, some fruits, legumes, and liver) compared to people living in low-risk regions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several evidence-based studies have also evaluated this association. For example, data from meta-analyses suggest that an increased consumption of folate may decrease the risk of EC, while increased total vitamin B6 levels may help prevent many types of cancers, including EC [ 9 , 10 , 11 ]. On the other hand, no meta-analysis has been performed to examine the association between dietary vitamin B2 and vitamin B12 intake and the risk of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dietary factors [7] may affect the risk of esophageal cancer. Previous studies suggested that vitamins intake [8,9], fiber intake [10], folate intake [11,12], could decrease the development of esophageal cancer. Intakes of bioactive compounds from various plant sources also reduced the risk of cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer remained an indispensable cause of cancer-related deaths and had shown a dramatic increase in global morbidity by more than six times [2]. Efforts to identify lifestyle factors [3] that may affect the risk of esophageal cancer had been ongoing, as well as some dietary factors, such as dietary vitamins [4,5], dietary fiber intake [6], dietary folate intake [7,8], total iron and zinc intake [9] and so on, may affect the development of esophageal cancer. Previous studies had been published to assess carbohydrate intake and some cancers risk, such as colorectal cancer [10], breast cancer [11], prostate cancer [12], but no meta-analysis was performed between carbohydrate intake and the risk of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%